2020
DOI: 10.3390/molecules25173916
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Silico and In Vitro Evaluation for Acetylcholinesterase and BACE-1 Inhibitory Activity of Some N-Substituted-4-Phenothiazine-Chalcones

Abstract: Acetylcholinesterase (AChE) and beta-secretase (BACE-1) are two attractive targets in the discovery of novel substances that could control multiple aspects of Alzheimer’s disease (AD). Chalcones are the flavonoid derivatives with diverse bioactivities, including AChE and BACE-1 inhibition. In this study, a series of N-substituted-4-phenothiazine-chalcones was synthesized and tested for AChE and BACE-1 inhibitory activities. In silico models, including two-dimensional quantitative structure–activity relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…They are regarded as the main forces acting as small ligands binding to receptors. Moreover, the combination of 2D and 3D models help to predict the biological activities of the proteins more accurately ( Tran et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They are regarded as the main forces acting as small ligands binding to receptors. Moreover, the combination of 2D and 3D models help to predict the biological activities of the proteins more accurately ( Tran et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kashyap et al observed that two plant natural compounds, reserpine and ajmalicine (Figure 7), also interacted with some of the most rele- Similar to what occurs for synthetic compounds, flavone derivatives (PDB#6EQM), specifically baicalein and diosmetin derivatives [57], 2-phenylbenzimidazoles (PDB#1FKN) [58], 7,8-dihydroxyflavone derivatives (PDB#2ZHS) [59], molecular hybrids of 2-pyridylpiperazine and 5-phenyl-1,3,4-oxadiazoles (PDB#2ZJM), especially compound 4 [60], and quinazolinonebased hydrazones (PDB#4B70) [61], also have demonstrated very promising in silico results that can result in novel drug candidates for BACE-1 inhibition, as shown in (Figure 8). Tran et al [62] built a 2D-QSAR model (R 2 of 0.83) based on the structure of BACE-1 inhibitors found in the literature to identify novel potential inhibitors in a library of chalcone derivatives. The highest-ranking hits were submitted to molecular docking against BACE-1 (PDB#5HU1) to select the most promising candidates [62].…”
Section: β-Secretasementioning
confidence: 99%
“…Tran et al [62] built a 2D-QSAR model (R 2 of 0.83) based on the structure of BACE-1 inhibitors found in the literature to identify novel potential inhibitors in a library of chalcone derivatives. The highest-ranking hits were submitted to molecular docking against BACE-1 (PDB#5HU1) to select the most promising candidates [62]. In particular, compound AC4 (Figure 8), a phenotiazine-chalcone derivative, displayed the highest affinity towards the target [62].…”
Section: β-Secretasementioning
confidence: 99%
See 1 more Smart Citation
“…Chalcones have attracted great research interest due to their numerous biological activities, such as antioxidant activity, anti‐inflammatory, antitumor, antimalarial, antimicrobial, analgesic, and neuroprotection activity [38–44] . Recent studies have also indicated that chalcone derivatives can inhibit Aβ aggregation moderately, and display antioxidation [45–48] . All the above showed that chalcone could be regarded as a starting molecule to design multifunctional drugs for curing AD.…”
Section: Introductionmentioning
confidence: 99%